SELF-INTEGRITY OF THE MAIN CHARACTER IN THE MOVIE THE RON CLARK STORY BY RANDA HAINES (A STUDY OF PSYCHOANALYSIS THEORY) - Tuti Apriani (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2019)
ABSTRACT This research examined the self-integrity of the main character in the movie The Ron Clark Story by Randa Haines. The focus of this research was to know the self- integrity through the portrayal of personality by using Carl Gustav’s psychoanalysis theory. This research used Jung’s psychoanalysis theory which focused on consciousness, personal consciousness, and collective consciousness. This research used qualitative method by taking steps using data collection, data analysis, and data presentation. The result of this research show that Ron Clark is a main character who has self-integrity because the personal consciousness and collective consciousness dominate more than his consciousness or ego. Key words: main character, self-integrity, psychoanalysis, and movie.